Krisis Epistemologi Pendidikan Islam di Era Modern: Systematic Literature Review tentang Dikotomi Ilmu dan Model Integrasi Keilmuan - Muhammad Arhandika Rahman; Aldi Ashaomi Saputra; Ahmad Sulhan (Mataram University, 2026)
Modernity has intensified the dichotomy between religious and general knowledge in Islamic education, leading to an epistemological crisis. This article aims to examine the historical and epistemological roots of this dichotomy, explore relevant models of knowledge integration, and formulate directions for reconstructing contemporary Islamic education. This study employs a qualitative approach with a systematic literature review design, involving an in-depth examination of relevant articles, books, and scholarly publications spanning the period from 1989 to 2026. The data were analyzed through thematic synthesis, focusing on the historical roots of dichotomy, critiques of modern epistemology, and models of knowledge integration. The findings show that the epistemological crisis in Islamic education is rooted in colonialism, the secularization of modern knowledge, dualistic educational systems, and the weakening of the tauhidic worldview. In contrast, Amin Abdullah’s integration-interconnection paradigm, bayani-burhani-irfani epistemology, the tauhidic approach, and Nasr’s idea of the desacralization of knowledge offer promising solutions. The study concludes that Islamic education requires a holistic, integrative, and transformative epistemological paradigm to respond to modern challenges without losing its spiritual and moral dimensions.